Сингулярно збурені нормальні оператори - Дудкін, М.Є. (Український математичний журнал, 1999)
Наведено узагальнення означення сингулярно збурених операторів на випадок нормальних операторів. Для цього використано ідею нормальних розширень передиормального оператора і доведено формулу для резольвент нормальних розширень типу М. Г. Крейиа для резольвент само-спряжеиих розширень. Крім цього встановлено взаємно однозначну відповідність між множиною сингулярних збурень рангу один і множиною сингулярно збурених (рангу один) операторів. We present a generalization of definition'of-singularly perturbed operators to the case of normal operators. To do this, we use an idea of normal expansions of a prenormal operator and prove the relation for resolvents of normal expansions similar to the M. Krein relation for resolvents of self-adjoint expansions. In addition, we establish one-to-one correspondence between the set of singular perturbations of rank one and the set of perturbed (of rank one) operators.